PEMODELAN MEKANISME GEMPA BUMI PADANG 2009 BERDASARKAN DATA SUGAR - Yusfania, Meiriska; Anjasmara, Ira Mutiara; Sanjiwani, I Dewa Amertha (Departemen Teknik Geomatika ITS, 2016)
Indonesia is located among three tectonic plates, namely Eurasia, Hindia-Australia and Pasific plate. It is affected some tectonic activities such as earthquake and volcano eruption at nearest tectonic zone. On September 31st 2009 around Padang, Pariaman, epicenter 99 52’1.2”E; 0 43’12”S, occurred an earthquake with magnitude 7.6 Mw and as one of disaster mitigation action in the earthquake zone societies, geodynamic analysis nowdays is needed in modelling the earthquake probability. Geodynamic study is easier to be completed by using continued GPS method. It can be analyzed the displacement at the earthquake phase. This research will examine modelling mechanism earthquake (coseismic) Padang 2009 by GPS continued method using GPS network Sumatran GPS Array (SuGAr) and dislocation model elastic half-space. The results showed that the biggest displacement happened in MSAI station with -6.26 mm on horizontal axis (easting, northing) and TLLU station with 20.83 mm on vertical axis (up). The most fit model for visualizing the mechanism earthquake Padang 2009 is model number 3 with the parameters of width 69 km, slipage -5 m and dipping angle 12.762 . Model number three represented mechanism earthquake Padang 2009 because the highest score of correlation which is -0.71965mm in horizontal displacement and 0.75906 in vertical displacements. It shows that earthquake mechanism that happened in Padang is Thrust Fault